2000
DOI: 10.1139/h00-005
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of Androstenedione Supplementation in Healthy Young Males

Abstract: We examined the effects of androstenedione supplementation on the hormonal profile of 10 males and its interaction with resistance exercise. Baseline testosterone, luteinizing hormone, estradiol, and androstenedione concentrations were established by venous sampling at 3 hr intervals over 24 hr. Subjects ingested 200 mg of androstenedione daily for 2 days, with second and third day blood samples. Two weeks later, they ingested androstenedione or a placebo for 2 days, in a double-blind, cross-over design. On da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 12 publications
0
39
1
Order By: Relevance
“…However, a single dose of 100 mg/day is insufficient to increase serum testosterone concentrations in men (1-4 ). Even with higher "recommended" doses of either 200 or 300 mg/day (given as either single or multiple administrations), no significant increase has been observed in most studies (1,3,5 ), albeit in one investigation, 4 of 14 men had testosterone concentrations that exceeded the reference interval (2 ). The contribution of these administered amounts of androstenedione to the plasma testosterone concentration appears to be relatively small compared with the large amount of testosterone secreted by the testes.…”
mentioning
confidence: 96%
“…However, a single dose of 100 mg/day is insufficient to increase serum testosterone concentrations in men (1-4 ). Even with higher "recommended" doses of either 200 or 300 mg/day (given as either single or multiple administrations), no significant increase has been observed in most studies (1,3,5 ), albeit in one investigation, 4 of 14 men had testosterone concentrations that exceeded the reference interval (2 ). The contribution of these administered amounts of androstenedione to the plasma testosterone concentration appears to be relatively small compared with the large amount of testosterone secreted by the testes.…”
mentioning
confidence: 96%
“…Based upon preplanned power analysis, assuming a 23 nmol L ¡1 increase in serum total testosterone concentrations due to SL-DIOL intake (Brown et al 2002) and a power of 80% with an level of 0.05 it was determined that six subjects could detect this magnitude of change. Similarly, assuming a 44 pmol L ¡1 increase in serum estradiol concentrations due to exercise in conjunction with androstenediol supplementation (Ballantyne et al 2000) and a power of 80% with an level of 0.05, it was determined that Wve subjects were required to detect this diVerence. Data are presented as means § SEM throughout the text.…”
Section: Calculations and Statisticsmentioning
confidence: 99%
“…Ingesting 100 or 200 mg doses of androstenedione Ballantyne et al 2000;Brown et al 2000b;Leder et al 2000;Rasmussen et al 2000) or androstenediol (Earnest et al 2000) does not acutely alter serum testosterone concentrations in eugonadol men. However, Leder et al (2000) observed that in 2 out of 14 healthy men who consumed a single dose of 300 mg androstenedione, serum testosterone concentrations were acutely elevated by as much as fourfold.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations